2019
DOI: 10.1073/pnas.1819663116
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of β-catenin/B cell lymphoma 9 protein−protein interaction using α-helix–mimicking sulfono-γ-AApeptide inhibitors

Abstract: The rational design of α-helix-mimicking peptidomimetics provides a streamlined approach to discover potent inhibitors for protein−protein interactions (PPIs). However, designing cell-penetrating long peptidomimetic scaffolds equipped with various functional groups necessary for interacting with large protein-binding interfaces remains challenging. This is particularly true for targeting β-catenin/ BCL9 PPIs. Here we designed a series of unprecedented helical sulfono-γ-AApeptides that mimic the binding mode of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
109
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 49 publications
1
109
0
Order By: Relevance
“…Histone PTMs have been shown to be important for many biological processes, including gene regulation, DNA repair, accurate genome organization, and DNA replication (Leach and Brown, 2012). Through mass spectrometry analyses, 26 and 16 histone Kla sites were identified from human and mouse, respectively (Zhang et al, 2019). In our study, the 273 Kla sites include 6 sites on histones, four of them conserved in human and two of them have not been reported thus far ( Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Histone PTMs have been shown to be important for many biological processes, including gene regulation, DNA repair, accurate genome organization, and DNA replication (Leach and Brown, 2012). Through mass spectrometry analyses, 26 and 16 histone Kla sites were identified from human and mouse, respectively (Zhang et al, 2019). In our study, the 273 Kla sites include 6 sites on histones, four of them conserved in human and two of them have not been reported thus far ( Supplementary Figure 3).…”
Section: Discussionmentioning
confidence: 61%
“…Alpha-helix structure is the most abundant secondary structure in proteins and often located at surface of core, with hydrophobic residues on inner-facing side, hydrophilic on other side. It is reported that alpha-helix structure is involved in a variety of functions including DNA binding, protein interaction, and stability of membrane proteins (Mckay et al, 2018;Manav et al, 2019;Sang et al, 2019). Thus, the preference of Kla on alpha-helix suggested a potential role of Kla in the above mentioned biological pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4] In particular, a-helix mediatedP PIs [8] have received attention, in part due to the defined structural component of binding conferred by docking of an a-helix from one protein into ac left on another, but also as ac onsequence of the regularp attern of hot-spot residues that are characteristic of such PPIs. [9][10][11] This has facilitated the development of constrained peptide [12][13][14][15] and foldamer based [16][17][18] topological mimics of the helix (i.e.,m imicking the local conformation of the helix), alongside topographical mimics [19][20][21][22][23] of the helix (i.e.,m imicking the surfacef eatures of the helix).…”
Section: Introductionmentioning
confidence: 99%